Causality of Credit Distribution in Indonesian Banking - Mustafa, Mustafa; Nurjaya, Muhammad; Fachmi, Muhammad (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study aims to examine the effect of third-party funds, Capital Adequacy Ratio (CAR), return on assets (ROA), Operating Expenses on Operating Income (BOPO), and NPL (Non-Performing Loans) on Credit Distribution to commercial banks listed on the Stock Exchange. Indonesian Securities for the period 2018-2021. The type of research used in this research is associative research. Associative research is research to know the relationship between two or more variables. Thus, Dabat builds a theory that functions to predict and control a phenomenon. The researcher explains whether TPF, CAR, ROA, BOPO, NPL, and Credit Distribution in this study. The population of this study is the banking sector companies listed on the Indonesia Stock Exchange, as many as 42 banks. The sample selection method used is purposive sampling. So the total sampled is 120 samples. The data were analyzed using multiple linear regression analysis with the Ordinary Least Square model using the Eviews Version 12 software. The results of this study found that Third Party Funds (DPK), Capital Adequacy Ratio (CAR), and Return on Assets (ROA) had a positive and significant effect on Credit Distribution to banking companies listed on the Indonesia Stock Exchange (IDX). Meanwhile, Operating Expenses on Operating Income (BOPO) and NPL (Non-Performing Loans) have a negative and significant effect on Credit Distribution to banking companies listed on the Indonesia Stock Exchange (IDX).